Inhibition of luminous Vibrio harveyi by "green water" obtained from broodstock and juvenile outdoor tanks of tilapia, Oreochromis mossambicus. - De La Cruz, Joana Joy Y. (Iloilo College of Fisheries, University of the Philippines in the Visayas, 2005)
This study investigated the antibacterial activity of the "green water" obtained from oreochromis mossambicus against vibrio harveyi and whether it is a potential alternative to tilapia hornorum. Containers with a capacity of 1 liter were filled with 750 ml of "green water" (collected from the broodstock and juvenile outdoor tanks), pond water and filtered boiled seawater that served as control. The containers were inoculated with Vibrio harveyi to a final density of 10³ cfu/ml. Results showed that luminous bacteria in "green water" obtained from the broodstock tank were completely inhibited after day 1 of inoculation with vibrio harveyi. This inhibition of the pathogen may be attributed to the microalgae, epidermal mucus and bacteria present in the "green water" of the broodstock tank. Another interesting finding was the delayed inhibition of luminescence in the "green water" obtained from the juvenile tank that lasted until day 3. This could be attributed to low mucus production and a not fully functional immune system of juvenile oreochromis mossambicus. This clearly indicates that the "green water" from the Juvenile tilapia is not as effective as the "green water" from broodstock tilapia. This study confirms the effectiveness of "green water" from the broodstock tank of Oreochromis mossambicus in the control of vibrio harveyi and showed that it is a potential alternative to Tilapia hornorum in the green water culture system.
Thesis (Undergrdauate, Bachelor of Science in Fisheries) College of Fisheries, University of the Philippines in the Visayas, 2005.
Keywords: Oreochromis mossambicus